Evaluation of the influence of the catalysts application on the level of emissions of carbon monoxide in the manufacture of electrodes - Ivanenko, Olena; Gomelya, Nikolai; Panov, Yevgen (Technology audit and production reserves, 2020)
The object of research is emissions harmful to the environment by the example of emissions from the manufacturer of electrodes of Ukrgrafit JSC (Zaporizhzhia, Ukraine). As well as carbon material, during the heat treatment of which the formation of carbon monoxide occurs, taking into account the use of the catalyst directly in the technological process of heat treatment of carbon material. Based on the simulation of dispersion of emissions of Ukrgrafit JSC in the air, taking into account the size of the sanitary protection zone, it is shown that the CO surface concentration, taking into account background pollution, exceeds the maximum permissible concentration (MPC) at control points. It is determined that in order to achieve the established standards at the border of residential development, it is necessary to modernize production by introducing scientific and technical solutions to protect the atmosphere from pollution by carbon monoxide. Physical modeling of the processes of heat treatment of carbon materials for the production of electrodes, such as bedding, granular pitch, charge for billets, in a laboratory setup is carried out. The thermal regime is evaluated for the level of carbon monoxide emissions during firing of carbon material. The results are compared with the data obtained by examining the parameters of the furnaces in the enterprise. The efficiency of using the catalyst directly in the technological process of heat treatment of carbon material to the efficiency of the oxidation of carbon monoxide is determined. It is established that a successful solution to the problem of exceeding the standard of carbon monoxide emissions in the technology for the production of electrodes is possible by using overfill modified with manganese dioxide with a MnO2 content of 1.5 %. It is shown that after the catalytic neutralization of carbon monoxide, the maximum CO surface concentration on the boundaries of housing taking into account background pollution does not exceed the maximum permissible concentration. This ensures that 0.576638 MPC is obtained from the value of the maximum one-time maximum permissible concentration of carbon monoxide, minimizes the environmental risks from the company's emissions for the population. Modernization of production by introducing a system of catalytic neutralization of carbon monoxide does not require special equipment, compared with well-known analogues it does not require significant investment.